PEMBINAAN KOMUNITAS BELAJAR GURU DALAM PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS POWTOON DAN E-MODUL - Putra, Ari Limay Trisno; Firdaus, Firdaus; Efendi, Nofriza (Jurnal Pemberdayaan Sosial dan Teknologi Masyarakat, 2024)
Abstract: Engaging learning will increase students' motivation and numeracy-literacy skills. Teachers' digitalization skills are needed in developing teaching media used in the learning process to achieve learning outcomes. The Teacher Learning Community is a forum for teachers to learn to solve problems faced in the learning process in the classroom. The need for a program to develop digitalization skills in making teaching media in the teacher learning community. The Teacher Learning Community Development Activity in Powtoon-Based Learning Media Development and E-Modules carried out by the community service team with funding from the Ministry of Education and Culture's DRTPM Grant is a solution. The activity was carried out for 4 meetings, namely Introduction to the Powtoon Application, Making or producing Powtoon Learning Media, Introduction to Sigil Software for making E Modules, Making or producing E Modules, Evaluation and mentoring Involvement of members and partner partners. At the evaluation and assistance stage of producing learning media, the results produced by the participants will be used by teachers in the learning process in their respective classes.Keywords: Learning Media, Powtoon, E-Module, Teacher Community Abstrak: Pembelajaran yang menarik akan meningkatkan motivasi dan kemampuan literasi-numerasi siswa. Kemampuan digitalisasi guru sangat dibutuhkan dalam mengembangkan media ajar yang digunakan pada proses pembelajaran untuk mencapai capaian pembelajaran. Komunitas Belajar Guru merupakan wadah guru dalam belajar menyelesaikan permasalahan yang dihadapi dalam proses pembelajaran di kelas. Perlunya program pengembangan kemampuan digitalisasi dalam pembuatan media ajar pada komunitas belajar guru. Kegiatan Pembinaan Komunitas Belajar Guru dalam Pengembangan Media Pembelajaran Berbasis Powtoon Dan E-Modul dilakukan tim pengabdian kepada masyarakat dengan pendanaan Hibah PKM DRTPM Kemendikbud menjadi sebuah solusi. Kegiatan dilakukan selama 4 kali pertemuan yaitu Pengenalan Aplikasi Powtoon, Pembuatan atau memproduksi Media Pembelajaran Powtoon, Pengenalan Sigil Soffware untuk pembuatan E Modul, Pembuatan atau memproduksi E Modul, Evaluasi dan pedampingan Keterlibatan anggota dan mitra Mitra. Pada tahap evaluasi dan pendampingan memproduksi media pembelajaran,  hasil yang diproduksi oleh peserta akan digunakan oleh guru dalam proses pembelajaran dikelas masing-masing.Kata kunci: Media Pembelajaran, Powtoon, E-Modul, Komunitas Guru